Investment protection in outer space - Laura Yvonne Zielinski (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
With investments in outer space growing exponentially and with more states seeking to develop domestic space capabilities, states should be aware of their rights and obligations under international space law and of the potential applicability of investment protection obligations to space investments and the standards of care expected from them.
Keywords: 330